Food selection in Microtus arvalis: the role of plant functional traits - Lantová, Petra; Lanta, Vojtěch (Ecological Research, 2008)
Abstract We offered captive common voles ( Microtus arvalis ) a choice of 11 plant species (representing four ecological groups) growing in vivaria. Selection was evaluated by measuring (1) the biomass of each plant species consumed and (2) functional and life‐history plant traits. The legume Trifolium pratense , known for its high nutrient level, and well accessible rosette forbs creating the highest biomass at the soil ground level, were mostly preferred. Voles avoided mainly grasses and the creeping forb Thymus pulegioides . The experiment showed that foraging was strongly plant species‐specific. We assessed whether plant functional traits explain selective foraging in common voles. To explore this, we reanalyzed Holišová's ( 1959 ) data about common vole stomach contents and plant trait databases. Regression tree analysis indicated that plant guild and life span were the best predictors of dietary selection, with a probability exceeding 0.5 that voles would eat more grasses and/or legumes than forbs. These results do not correspond with the feeding trial. We suggest that the voles usually consume grasses in the field because grasses are abundant and readily available, but prefer protein‐rich forbs when possible.